Satisfaction on Nursing Management of Postoperative Complications Rendered by Surgical Staff Nurses at Four Hospitals in Iriga City, Philippines - Modesto P. Fucio (Camarines Sur Polytechnic Colleges, 2023)
This study aimed to determine the level of satisfaction of surgical staff nurses and clients on the nursing management of postoperative complications rendered by the staff nurses in the different hospitals in Iriga City. This study specifically aimed to determine the personal and professional attributes of the surgical staff nurses in terms of age, gender, educational attainment, seminars or training, and years of experience in the surgical area; to determine the level of satisfaction with the nursing care for preventing postoperative complications along nursing care, early ambulation, adequate nutrition, skin breakdown, and pressure source, adequate pain management; to determine if there a significant difference on the level of satisfaction on the nursing care for preventing post-operative complications of the patients and the nurses; to determine if is there a significant relationship between personal and professional attributes and interventions rendered by the surgical staff nurses; and to identify measures that can be proposed based on the findings of the study. The study is descriptive-correlational research. Frequency count, percentage techniques, weighted means, and the Wilcoxon Rank-Sum Test of Two-Sample Test were employed as statistical tools. The result showed that a majority of the surgical staff nurses' age ranges from 25 years old and below, mostly female, baccalaureate degree holders, 6 to 10 years in service, and attended training in the surgical area. Staff nurses and patients are much satisfied with the nursing management in preventing postoperative complications. Likewise, there is no significant difference in the level of satisfaction between the clients and the staff nurses in post-operative complications. Also, there is no significant relationship between the profile of the staff nurses and the level of satisfaction with the nursing care of preventing post-operative complications of the patients. A Postoperative Management Brochure was developed to serve as a guide for effective postoperative care.